Adrenal Crisis In A Patient With An Adrenal Tumor - Amirullah, Muamar; Novida, Hermina (Journal of Neonatal Surgery, 2025)
Sudden and dangerous hormone deficiency from the adrenal glands can lead to a critical medical emergency known as adrenal crisis, which may result from adrenal tumors. This case report presents a 63-year-old woman diagnosed with an adrenal crisis due to Addison’s disease secondary to an adrenal tumor. The patient experienced progressive weakness, nausea, vomiting, and significant electrolyte imbalances, particularly severe hyponatremia (104 mmol/L). Laboratory findings showed low morning serum cortisol levels (16.5 ng/mL) and elevated ACTH levels (152.7 pg/mL), confirming primary adrenal insufficiency. Imaging revealed bilateral adrenal masses, suggesting hyperplasia or adenoma. The patient was treated with intravenous hydrocortisone, fluid resuscitation, and electrolyte correction, which resulted in clinical improvement. She was later transitioned to oral hydrocortisone and scheduled for adrenalectomy. Based on this case report, diagnosing adrenal insufficiency is difficult due to its vague symptoms, often leading to delayed recognition and increased risk of death. Prompt recognition and management of adrenal crisis is critical for better patient survival.